Skills, qualifications and jobs in the EU: the making of a perfect match? : evidence from Cedefop's European skills and jobs survey - (:unkn) unknown (Publications Office of the European Union, 2015)
"What has been the impact of the economic crisis on skill mismatch? Is there a cost in getting the unemployed quickly into any job? Why is skill mismatch prevalent among the EU workforce? To answer these and other timely questions on skill mismatch, in spring 2014 Cedefop carried out the European skills and jobs (ESJ) survey. The findings caution that the prolonged economic downturn is threatening the long-term potential of the EU human resources. A greater share of recent job finders has entered into jobs that need lower qualifications and skills than their own. The unemployed also run a greater risk of misplacement into jobs of lower skill intensity. More than one in five EU employees has not developed skills since they started a job, as over one third of EU jobs are characterised by poor task complexity and lack of continued learning. Closer stakeholder collaboration and policy action is needed in the EU to generate not only more skills but also, crucially, better jobs for better-matched skills." (Editor, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.3.1 Potenziale; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.2 Europa; Arbeitsmarkt; Arbeitskräfteangebot; Berufliche Qualifikation; Qualifikationsbedarf; Mismatch; Unterqualifikation; Überqualifikation; Einflussfaktor; Qualifizierungsmaßnahme; Lernen am Arbeitsplatz; Schlüsselqualifikation; Europa